2022
DOI: 10.2147/opth.s347382
|View full text |Cite
|
Sign up to set email alerts
|

The Vivity Extended Range of Vision IOL vs the PanOptix Trifocal, ReStor 2.5 Active Focus and ReStor 3.0 Multifocal Lenses: A Comparison of Patient Satisfaction, Visual Disturbances, and Spectacle Independence

Abstract: Purpose To compare patient-reported outcomes (PROs) after intraocular lens (IOL) implantation with the AcrySof IQ Vivity IOL or Vivity Toric IOL to those achieved with other multifocal IOLs. Patients and Methods Prospective, open-label, multicenter analysis of PROs, including spectacle independence, dysphotopsia, and overall satisfaction among patients who underwent cataract surgery at least 1 month previously with bilateral Vivity or Vivity Toric lenses (n=60). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…A recent study comparing AcrySof IQ Panoptix, a quadrifocal IOL, with the AcrySof IQ Vivity IOL described that the former provided greater near visual acuity than the AcrySof IQ Vivity IOL. 16 Furthermore, the mini-monovision technique has reportedly been used to improve near vision using EDoF IOLs. [17][18][19][20] Amelsfort et al 17 reported that when they adjusted emmetropia in the dominant eye and slight myopia in the nondominant eye (−0.25 D to −0.50 D), patients reported improved near visual acuity, better satisfaction, and higher spectacle independence.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study comparing AcrySof IQ Panoptix, a quadrifocal IOL, with the AcrySof IQ Vivity IOL described that the former provided greater near visual acuity than the AcrySof IQ Vivity IOL. 16 Furthermore, the mini-monovision technique has reportedly been used to improve near vision using EDoF IOLs. [17][18][19][20] Amelsfort et al 17 reported that when they adjusted emmetropia in the dominant eye and slight myopia in the nondominant eye (−0.25 D to −0.50 D), patients reported improved near visual acuity, better satisfaction, and higher spectacle independence.…”
Section: Discussionmentioning
confidence: 99%
“…98 The most complained postoperative visual discomfort were halos and glares, with that it was included in a score range of high satisfaction and tolerability of this IOL 98 and the dysphotopsia profile is significantly better in the Vivity lens when compared with MFs. 102 In a study performed by our research group, evaluating the quality of the retinal optical image following implantation of the Vivity EDOF IOL and compared with a monofocal and a trifocal IOL, it was found that although trifocal IOLs provided significantly better retinal image quality, this IOL also demonstrated to be the most sensitive to residual refractive errors. Both Vivity and monofocal IOLs showed a comparable retinal image quality.…”
Section: Type 3-mf With Low-power Near-vision Additionmentioning
confidence: 99%
“…17,18 In addition, the Vivity IOL has been reported to provide less visual disturbances compared with multifocal IOLs. 19…”
mentioning
confidence: 99%